Investigation for Influences of Seepage on Mechanical Properties of Rocks Using Acoustic Emission Technique - Saisai Wu; Xiaohan Zhang; Junping Li; Zhao Wang (Geofluids)
The behavior of rock mass is governed by the properties of both the rock material and discontinuities in the rock mass. Surrounding environments including the existence of water also have a great influence on the behavior and mechanical properties of rocks. In this study, a novel-designed compression and seepage testing system, associated with an acoustic emission system, was designed and constructed. The changes in the specimens resulting from the uniaxial compression were monitored by an acoustic emission technique. The characteristics of the acoustic emission parameters at different stages including compaction and crack initiation, crack propagation, and catastrophic failure were analyzed. The existence of seepage had direct influences on the mechanical properties and failure patterns of the specimens. The specimens tested in pure compression conditions demonstrated strong burst proneness and ruptured into separate pieces, while for the specimens with seepage, no burst proneness was observed and the specimens tended to fail along a macroscopic shear failure plane. The highest average energy of the acoustic signal occurred at the stage of initial rupture of rock specimens, rather than at the stage of widespread rupture. The studies explored the possibilities of using the acoustic emission technique to investigate the problems associated with the seepage in geotechnical and rock engineering and provided meaningful results for further research in this field.